The efficacy of problem-based learning of plus-size design in the fashion curriculum. Issue 1 (2nd January 2016) - Christel, Deborah A.
Abstract : As obesity rates have grown in the past decades, so has interest in plus-size fashion. With more than 50% of US and Canadian women reporting that they wear a size 14 or higher, it is critical to address this demographic. To respond to this trend, fashion designers and merchandisers have been encouraged to incorporate plus-sizes into their lines [Kim, H. Y., Jolly, L., & Kim, Y. K. (2007). Future forces transforming apparel retailing in the United States: An environmental scanning approach. Clothing and Textiles Research Journal, 25 (4), 307–322. 10.1177/0887302X07306851)]. Plus-size options are available although there are challenges for apparel designers and merchandisers when trying to create the ideal fit and inviting retail experience. To help undergraduate apparel students gain confidence, learn about critical issues and problem-solving approaches for the plus-size market, a project was created and implemented in an undergraduate design course at a US university in the Pacific Northwest. In the course, using the problem-based learning method, students researched, designed and produced an original plus-size prototype swimsuit for a prominent competitive swimwear company. Student feedback following the project was largely positive, with most students demonstrating increase in confidence and necessary skills through a hands-on approach.